Study on appropriate warehousing and collateral management systems in sub-Saharan Africa - Volume 3 - Review of applicable laws - Agence Française de Développement; Technical Centre for Agricultural and Rural Cooperation; International Fund for Agricultural Development (AFD / CTA / IFAD, 2014)
Farmers throughout the developing world face considerable challenges in accessing finance, and this can often influence their decision-making. These challenges must be addressed with financing solutions tailored to the different actors of the agricultural value chain. Warehouse receipt financing enables the post-harvest part of the value chain to function more efficiently and is a potentially useful tool for helping farmers access to funding. This is the core subject of this report.